Particle tracking simulation of an air channel transistor - Mahta Monshipouri (AIP Publishing LLC, 2021)
Advances in nanofabrication techniques have underpinned the recent growing interest in vacuum channel transistors due to their ability to showcase ballistic transport and immunity to most radiations. However, the geometry of the electrodes plays an important role in the overall performance and efficiency of the device. Several studies on the geometry of the source electrode have been carried out because of its role in enhancement of the local electric field, which triggers electron tunneling, yet the geometry of the drain electrode has been neglected. Here, we propose a new planar vacuum channel transistor with gold electrodes. Our study shows that the unique geometrical design of the device leads to high collection efficiency. Furthermore, it reveals the importance of the geometry of the drain on device performance. Emission characteristics of the device and the effect of geometrical parameters such as channel length and source geometry on its performance have also been investigated.